Potret Kucing sebagai Hasil Fantasi Patriarki dari Puisi “Ngiau” Karya Sutardji Calzoum Bachri - Mukafi, Muhammad Hamdan; Wahyuningsih, Triyanti (Sabda: Jurnal Kajian Kebudayaan, 2020)
Literary works are able to evolve their meaning in relation to the presence of an illustration embedded in them. Like the poem "Ngiau" by Sutardji Calzoum Bachri, which in this research is side by side with the illustration of a cat. The poem is able to absorb realist meanings aesthetically reflecting on the presence of cat illustrations embedded in it. Moreover, the illustration also reinforces the representation of reality that boils down to the perpetuation of patriarchy. In this case, the poem that comes with an illustration has a problematic representation of patriarchy that requires a long analysis of it. Aesthetically, the illustrative cat reinforces the fantastical representation of the patriarchal context in the poem "Ngiau". Cats are commonly known as highly populated creatures that can live in long alleys. This context makes patriarchy something that has been reflected in perpetuity because of the cat's attitude that places itself as the holder of a structure over the mouse as its prey, like a man who controls a woman's choice of things. The representation is meant to see how a concept of patriarchy has lived latently and blurred who is human and who is animalKarya sastra mampu mengevolusikan maknanya berkaitan dengan kehadiran suatu ilustrasi yang disematkan kepadanya. Seperti puisi “Ngiau” karya Sutardji Calzoum Bachri yang dalam penelitian ini berdampingan dengan ilustrasi kucing. Puisi tersebut mampu menyerap makna-makna realis secara estetik bercermin pada kehadiran ilustrasi kucing yang disematkan kepadanya. Terlebih, ilustrasi yang hadir sekaligus menguatkan representasi realita yang bermuara pada langgengnya patriarki. Dalam hal ini puisi yang hadir bersama suatu ilustrasi memiliki sebuah problematika representasi patriarki yang membutuhkan analisis panjang terhadapnya. Secara estetik, kucing yang hadir secara ilustratif menguatkan representasi fantasi dari konteks patriarki dalam puisi “Ngiau”. Kucing umum dikenal sebagai makhluk yang berpopulasi tinggi dan bisa hidup di gang-gang panjang. Konteks ini membuat patriarki sebagai sesuatu yang telah tercermin langgeng oleh sebab sikap kucing yang menempatkan dirinya sebagai pemegang suatu struktur di atas tikus sebagai mangsanya, seperti laki-laki yang menguasai pilihan perempuan atas suatu hal. Representasi tersebut dimaksud untuk melihat bagaimana sebuah konsep patriarki telah hidup dengan laten dan mengaburkan siapa manusia siapa hewan.